Latent classes of eating disorders and addictions by sex: Implication of alexithymia and stressful life events in youths - Macía, Laura; Momeñe López, Janire; Macía, Patricia; Herrero, Marta; Jauregui, Paula; Iruarrizaga, Iciar; Estévez, Ana (Frontiers in Psychology, 2023)
Introduction Eating disorders (EDs) and behavioural addictions show common psychological vulnerability factors such as alexithymia and stressful life events (SLE). This study aims, firstly, to explore the prevalence and latent profiles of participants based on their risk of suffering EDs, gambling disorder (GD), alcohol and/or drug abuse, and compulsive buying (CB) by sex. Secondly, it aimed to test whether alexithymia and having experienced SLE are associated with group membership. Methods The sample was predominantly drawn from university students and social networks. It was composed of 352 young adults between 18 and 35 years old, of whom 77.8% were women and 22.2% men. Results The results showed that the most prevalent disorders of the sample were alcohol, EDs, CB, drugs and GD, respectively. Moreover, latent class analyses were conducted based on the risk of suffering EDs or addictions by sex. Three main profiles were found: ‘Men with addictions’, ‘Healthy women’ and ‘Women with EDs’. Finally, differences in SLE and alexithymia levels were tested by latent classes. “Men with addictions” and “Women with EDs” had higher scores on alexithymia and SLE than the group of “Healthy women”. However, the group of “Women with EDs” (class 3) reported significantly higher levels of SLE and alexithymia than the other two groups. Discussion and conclusion In conclusion, we discuss the possibility that some vulnerability factors operate generally and transdiagnostically in EDs and addictive disorders. The identification of clinical phenotypes could complement and deepen prediction, prevention and treatment research in clinical settings. The need to take sex and gender differences into account is reinforced.